Making sense of statistics a non-mathematical approach - Wood, Michael (Palgrave study guides, 2003)
Introducing statistics and probability without the distractions of mathematics, this accessible text explains how and why methods work, and exactly what answers mean. Guidance is provided on how to design investigations, analyze data and interpret results.